Impedance Characteristics of Pulsed Atmospheric Electrical Discharge in Spherical Plasma Switch - Baghdad Science Journal (مجلة بغداد للعلوم)
A number of pulsed experiments have been carried out using a high-voltage circuit containing R,L, and C in certain arrangements. A spherical spark gap of steel electrodes was used as a high-current switch operated by a voltage of up to 8kV and triggered in both self-triggering and third-electrode triggering modes. Current measurements were carried out by using both current-viewing resistor and Rogowski coils designed for this purpose. Typical current waveforms have shown obvious dominating inductance effect of the circuit components in an underdamped oscillation. The behavior of the circuit impedance was studied by recording both pulsed current peaks and the charging voltages when currents of up to 2.5kA were recorded. The duration of these current pulses were found to extend between 0.1?s and 0.3?s depending on the values of the circuit components as well as the spacing of the spark gap electrodes along which the plasma propagates at atmospheric pressure. Over the whole range of experimental conditions, the average nominal impedance values were ranged between (2-10)? depending on the gap and circuit parameters. Typical damage patterns were observed with average diameters of up to 8.3 mm on the high voltage electrode and 10.5 mm on the grounded sphere resulting from accumulative discharges and power dissipation within the gap.